The Arras Witch Treatises : Johannes Tinctor's Invectives contre la secte de vauderie and the Recollectio casus, status et condicionis Valdensium ydolatrarum by the Anonymous of Arras (1460) - Anonymous of Arras; Tinctor, Johann, approximately 1405-1469; Pageau, François V., 1963-; Pageau, François V., 1963-; Desjardins, Robert B. (Robert Byron), 1969-; Desjardins, Robert B. (Robert Byron), 1969-; Gow, Andrew Colin; Gow, Andrew Colin (Book collections on Project MUSE., 2016)
"English translations of two major treatises, Tinctor's Invectives and the anonymous Recollectio, that arose from the famous Arras witch hunts and trial in the mid-fifteenth century in France"--Provided by publisher